PENGARUH HARGA, KEPERCAYAAN DAN CITRA MEREK TERHADAP KEPUASAN SISWA/I BERSEKOLAH DI SMK (SMIP) TAMAN WISATA CILEUNGSI KAB.BOGOR - Al Agus Kristiadi; Sharah Sarlita Ariyani Putri (LPPM Universitas Asa Indonesia, 2018)
This study aims to determine: the influence of price (X1), trust (X2) and brand image (X3) simultaneously or partially to customer satisfaction (students) choosing SMK (SMIP) Taman Wisata Cileungsi. This research is a descriptive research using quantitave approach. The research sample is 96 students at SMK (SMIP) Taman Wisata Cileungsi. This research is using purposive sampling and direct give questioner to students at SMK (SMIP) Taman Wisata Cileungsi also using descriptive analyze and multiple linear regression for analyzing data research. Result of the research showed that trust (X2) and brand image (X3) has significant effect on customer satisfaction (students), while price (X1) has unsignificant effect on customer (students) satisfaction. Beside that by simultaneous price (X1), trust (X2) and brand image (X3) has significant effect on customer satisfaction (students) choosing SMK (SMIP) Taman Wisata Cileungsi. Thus, SMK (SMIP) Taman Wisata Cileungsi should continue to improve the trust and brand image and than more pay attention about price, so that students are satisfied in SMK (SMIP) Taman Wisata Cileungsi.